KAJIAN SASTRA ANAK: KONTRIBUSI NILAI PERSONAL DAN NILAI PENDIDIKAN DALAM BUKU CERITA SI BUNCIR KARYA ASEP RAHMAT HIDAYAT - Rohmah, Dwi Putri Khabibatur; Putri, Aurelia Theysa; Agustian, Muhammad Ilham; Erfansyah, Muhammad; Setiawaty, Rani (Universitas Muria Kudus, 2024)
This study aims to analyze the personal values and educational values contained in the children's story